Perlindungan Pemutusan Hubungan Kerja (PHK) Terhadap Pekerja Perempuan - Srinorindra Rahayu Budiiswanti; Fence M. Wantu; Avelia Rahma Y. Mantali (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
This study aims to analyze legal protection for female workers who are laid off (PHK) and to find solutions to obstacles in providing legal protection for female workers who are laid off (PHK). The methodology used in this study is normative legal research, while the research approach used is a legislative approach where the relevant laws and decrees are sought and studied, and other decisions related to the legal issues being studied are matched by discussing thoughts and lessons or teachings in the field of law, and matching the formulation of the problem based on cases in the world of work related to the material being discussed. The results of the study indicate that various legal instruments, both national and international, have regulated protection for female workers, especially in situations of layoffs. Law No. 13 of 2003 concerning Manpower and the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) which has been ratified by Law No. 7 of 1984 have provided a clear legal basis regarding the prohibition of layoffs against women on the grounds of pregnancy, childbirth, or marriage. In addition, compensation and industrial dispute resolution are also regulated to ensure that the rights of female workers are protected. However, there are still gaps in the implementation of this legal protection, especially related to the lack of knowledge of workers regarding their rights and the uneven implementation of policies in various industrial sectors. Implementation obstacles in regulating the legal protection of female workers, namely work agreements that are not in accordance with regulations, the lack of general sanctions, and workers' ignorance of their rights are obstacles. The state needs to integrate international conventions into national law and ensure that violators receive appropriate sanctions. Many female workers are not yet fully aware of their rights, which hinders effective protection.